Investigation and application of a high performance grouting material in water-rich silty fine sand stratum. (25th April 2022) - Cui, Ying; Tan, Zhongsheng; Han, Deqiang; Song, Jianrong
Highlights: High-performance grouting material (DS grout) for water-rich silty fine sand stratum was prepared with sodium silicate and diacid ester. The DS grout has adjustable setting time, high strength, high durability and non-toxicity. The DS grout can effectively penetrate into water-rich silty fine sand stratum and form high strength sand solidification body. Abstract: Grouting reinforcement of water-rich silty fine sand stratum is a key and difficult problem in the construction of tunnel and underground engineering. In this paper, a kind of high-performance grouting material (DS grout) for water-rich silty fine sand stratum was prepared by using sodium silicate as the base material and diacid ester as the curing agent. The results show that the DS grout has adjustable setting time, high strength and high durability. The reaction mechanism of sodium silicate and curing agent was studied by infrared spectroscopy (IR) and scanning electron microscope (SEM). The acid generated from the hydrolysis of diacid ester reacted with sodium silicate solution and polymerized to generate silica gel. Through the grouting model experiment, the grouting effect of DS grout and phosphate-sodium silicate grouting material was compared. In addition, DS grout was used to reinforce the face of tunnel in water-rich silty fine sand stratum. The results show that DS grout can effectively penetrate into water-rich silty fine sand stratum and form high strength sand solidification body.